Reducing Heat Loss From Solar Hot Water Storage Tanks Using Passive Baffles - Paing, ST; Anderson, TN; Nates, RJ (Elsevier BV, 2022)
Solar water heating systems with thermal storage are one of the simplest ways of reducing energy demand for domestic water heating. Over the years, researchers have attempted to improve the thermal performance of storage tanks using various means, including baffle-type devices to control mixing during charging and discharging of the tank. However, one modification that has been overlooked is the use of passive baffles that suppress the natural convection inside the tank with a view to reducing their standing heat loss. Considering this, this study examined the use of concentric vertically mounted baffles on the natural convection inside a vertical cylindrical storage tank. To this end, a numerical model of a tank with a baffle was developed using computational fluid dynamics (CFD) and validated using experimental data. The results showed that a simple concentrically mounted baffle could reduce the natural convection heat transfer coefficient by up to 40%.
Keywords: Thermal storage; Heat loss; Natural convection; Convection suppression